Contribucion al estudio de la avifauna extinguida del Pleistoceno de la Republica Argentina (Ameghiniana, 2013)
The author describes a new extinguished species (Pionus ensenadensis) from the order Psittaciformes, on the grounds of the discovery of a left humerus, well preserved and practically entire, in the Lower Pleistoceno Strata (Ensenadan), outcropping in Olivos, Province of Buenos Aires, Argentina. He makes a comparison among known species of living parrots, finding the greatest similarities with the genus Pionus. This genus is largely distributed in America from Mexico to Bolivia, Paraguay, Southern Brazil and Argentina. Sub-species of Pionus maximiliani (Kuhl), are those which reach the most sou thern latitude in our country (Corrientes and Santa Fe provinces). Then the new discovery shows that during the Lower Pleistocene at least the genus had a larger southwards geographical expansion (Rio de la Plata region).